100th Anniversary of the Salzburg Festival: Historical and Cultural Phenomenon of the 20th and Early 21st Centuries - Rizaieva, Ganna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
Relevance of the study. The evolution and the very phenomenon of the Salzburg Festival go hand in hand with the history of music and theatre, the philosophy of art, and the global musical infrastructure of the 20th and early 21st centuries. On the one hand, it is their fair reflection; while on the other hand, it is an integral part of their development. That is why studying and understanding the role and place of the Salzburg Festival is essential for understanding contemporary musical culture in a current historical perspective. Relevance of the study is attributable to the fact that, for the first time in Ukrainian historical musicology, the development and implementation of the idea of holding the Salzburg Festival are considered, indirect relations between the festival ideologists and the Ukrainian cultural space at the turn of the 19th and 20th centuries are discovered, and the century-old history of the main European music and theatre forum is systematized. Main objective of the study is to introduce the phenomenon of the Salzburg Festival as a historical and cultural integrity in the space of the Ukrainian musicological discourse, as well as to outline and systematize a one hundred-year path of the main music and theatre forum in Europe. Methodology of the study includes the use of historical, culturological, and systemic approaches. Results and conclusions. The study revealed that at the stage of shaping the idea of the festival in Salzburg at the beginning of the twentieth century, there were two fundamental visions of its implementation, namely, “Mozart-oriented” and “general theatrical”. They both entered the gene code of the Salzburg Music and Theatre Forum with varying interpretations of its concept and repertoire policy at each phase of its existence. The change of priorities in its fundamental triad, that is, drama — opera — concert, during forum varying periods is also traced. The hundred-year journey of the Salzburg Festival may be divided into three main stages: 1) the development and search of self-identity (1920–1954); 2) “stabilization” and formation of international prestige (1955–1990); and 3) “modernization” and expansion of cultural horizons (from 1991 until today). Each of them is well integrated into history of Western European music and culture of the 20th and early 21st centuries.